A Station Selection Model Considering Intra-board Deformation and Strain Visualization Analysis - Chengcheng Fan (The International Journal of Multiphysics, 2024)
Computer visualization can intuitively reflect the process and results of crustal deformation. In this paper, taking into account the intraplate deformation, combined with computer visualization technology, using robust estimation method that can identify data with high collapse pollution rate, combined with the overall rotation and linear strain model (RELSM) that describes block movement, the GPS observation velocity field data of the Chinese Mainland tectonic environment monitoring network located in Ordos and its adjacent areas are screened, and the strain data are calculated to generate visual images for analysis. The results show that the method proposed in this paper can effectively consider the smoothness of internal plate deformation and the differences in local structures, suppress gross errors, and obtain good velocity field fitting results.